The Existence of Leptospira interrogans on Rats and The Transmission Potency in Public Areas: School, Traditional Market, and Settlement in Yogyakarta - Wibawaning Astuti, Raden Roro Upiek Ngesti; Yuangga, Salsabila Rifda; Fahrunniam (Indonesian Journal of Tropical and Infectious Disease, 2023)
Leptospirosis is a zoonotic disease caused by bacterial infection, Leptospira interrogans. Indonesia is known for being an endemic country of this disease and Yogyakarta Special Province has become one of the regions with high cases of Leptospirosis. There was lack of information on the L. interrogans prevalence on rats at the public areas, such as school and traditional market. This research was conducted to determine and predict the potential Leptospirosis transmission in public areas, especially in schools, traditional markets,. and the settlement of Yogyakarta. Wild rats were collected from several public places (elementary schools, traditional markets, and Settlement areas) by using single live traps. The rat's blood was centrifuged to obtain the serum. The serum was tested by using immunochromatography of Leptotek Lateral Flow. The collected rats and shrews were euthanized and then identified for the species and the morphological features. Total of 27 rats (67.5%) and shrews 13 (32.5%) were collected. There were six species of collected rats, namely Rattus argentiventer, Rattus norvegicus, Rattus tanezumi, Rattus tiomanicus, and Bandicota bengalensis, while the collected shrew species was Suncus murinus. The rats and shrews from traditional market were negative with L. interrogans, however the positive results was in elementary schools (14.28%), that were from R. norvegicus and S. murinus, moreover the positive infection also showed in the settlements (57.14%), that were from R. argentiventer, R. norvegicus, and R. tiomanicus. These findings indicated that school and settlement must be a concern for the leptospirosis transmission.